Association Between Dynamic Change of QT Interval and Long-Term Cardiovascular Outcomes: A Prospective Cohort Study - Ye, Min; Zhang, Jing-Wei; Liu, Jia; Zhang, Ming; Yao, Feng-Juan; Cheng, Yun-Jiu (Frontiers in Cardiovascular Medicine, 2021)
Background: The prolongation or shortening of heart rate-corrected QT (QTc) predisposes patients to fatal ventricular arrhythmias and sudden cardiac death (SCD), but the association of dynamic change of QTc interval with mortality in the general population remains unclear. Methods: A total of 11,798 middle-aged subjects from the prospective, population-based cohort were included in this analysis. The QTc interval corrected for heart rate was measured on two occasions around 3 years apart in the Atherosclerosis Risk in Communities (ARIC) study. The ΔQTc interval was calculated by evaluating a change in QTc interval from visit 1 to visit 2. Results: After a median follow-up of 19.5 years, the association between the dynamic change of QTc interval and endpoints of death was U-shaped. The multivariate-adjusted hazard ratios (HRs) comparing subjects above the 95th percentile of Framingham–corrected ΔQTc (ΔQTcF) (≥32 ms) with subjects in the middle quintile (0–8 ms) were 2.69 (95% CI, 1.68–4.30) for SCD, 2.51 (1.68–3.74) for coronary heart disease death, 2.10 (1.50–2.94) for cardiovascular death, and 1.30 (1.11–1.55) for death from any cause. The corresponding HRs comparing subjects with a ΔQTcF below the fifth percentile (<-23 ms) with those in the middle quintile were 1.82 (1.09–3.05) for SCD, 1.83 (1.19–2.81) for coronary heart disease death, 2.14 (1.51–2.96) for cardiovascular death, and 1.31 (1.11–1.56) for death from any cause. Less extreme deviations of ΔQTcF were also associated with an increased risk of death. Similar, albeit weaker associations also were observed with ΔQTc corrected with Bazett's formula. Conclusions: A dynamic change of QTc interval is associated with increased mortality risk in the general population, indicating that repeated measurements of the QTc interval may be available to provide additional prognostic information.